2015
DOI: 10.1177/0885066615618189
|View full text |Cite
|
Sign up to set email alerts
|

Is Admission to the Intensive Care Unit Associated With Chronic Opioid Use? A 4-Year Follow-Up of Intensive Care Unit Survivors

Abstract: Admission to ICU and duration of ICU stay were not associated with chronic opioid use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 29 publications
2
41
0
1
Order By: Relevance
“…25 There is evidence from surgical populations that pre-surgical opioid use is associated with an increased risk of postoperative opioid use and misuse, 98 and a large retrospective epidemiological study in Canada identified pre-admission opioid use (in 6.2% of admissions) was a significant predictor of opioid use at 1 yr post-ICU discharge. 99 A further study showed that 5% of the elderly population admitted to the ICU was taking chronic opioids and that 63% continued to use them post-discharge. Those most likely to continue opioids were medical patients who were using fentanyl and benzodiazepines at admission.…”
Section: Potential Risk Factorsmentioning
confidence: 99%
“…25 There is evidence from surgical populations that pre-surgical opioid use is associated with an increased risk of postoperative opioid use and misuse, 98 and a large retrospective epidemiological study in Canada identified pre-admission opioid use (in 6.2% of admissions) was a significant predictor of opioid use at 1 yr post-ICU discharge. 99 A further study showed that 5% of the elderly population admitted to the ICU was taking chronic opioids and that 63% continued to use them post-discharge. Those most likely to continue opioids were medical patients who were using fentanyl and benzodiazepines at admission.…”
Section: Potential Risk Factorsmentioning
confidence: 99%
“…For analysis of chronic post ICU pain (CPIP) and chronic opioid use after ICU, articles were excluded if they didn’t clearly state in the methods that patients were treated in the ICU, that included pediatric patients, that did not clearly refer to chronic pain and chronic opioid use after ICU discharge. Nine articles were included for analysis of chronic pain after ICU (Granja et al, 2002; Boyle et al, 2004; Korošec Jagodič et al, 2006; Jenewein et al, 2009; Timmers et al, 2011; Battle et al, 2013; Griffiths et al, 2013; Choi et al, 2014; Baumbach et al, 2016) and one article for chronic opioid use (Yaffe et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Chou et al (2009) adapted Von Korff et al (2008) definition of chronic opioid therapy as “daily or near-daily use of opioids for at least 90 days, often indefinitely.” One study was identified that considered opioid use following ICU discharge. Yaffe et al (2017) investigated opioid use in ICU survivors with surgical and non-surgical diagnoses by retrospectively analyzing electronic patient charts. They identified opioid use in 12.2% of patients at hospital discharge.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies will be included if they satisfy the following criteria, based on a PICO format question: studies with adults aged 18 years or older, on long-term or chronic opioid therapy (intending to reflect use of prescribed opioids more than 70% of days for at least 3 months [29] and that present to an acute healthcare setting secondary to a complication of prescribed opioid use; that include an intervention representing a harm reduction strategy, as defined as an attempt to decrease adverse consequences of long-term opioid use; that either compare the efficacy of the different interventions between each other or of individual interventions compared to current care; and that address patient or system related outcomes (e.g., ED visits, hospitalization, ICU admission, economic considerations).…”
Section: Methods and Analysismentioning
confidence: 99%